Ethylene Scavenging Films Based on Ecofriendly Plastic Materials and Nano-Tio2: Preparation, Characterization, and in Vivo Evaluation - Rodriguez-Mercado, F; Bruna-Bugueno, J; Valenzuela-Bascunan, X; Torres-Mediano, A (Multidisciplinary Digital Publishing Institute (MDPI), 2024)
It is known that ethylene plays an important role in the quality characteristics of fruits, especially in storage. To avoid the deterioration of fruits caused by ethylene, titanium dioxide (TiO2) has been used due to its photocatalytic capacity. The aim of this study was to develop films based on two types of biopolymers, Mater-Bi (MB) and poly-lactic acid (PLA), with nanoparticles of TiO2 and to determine their ethylene removal capacity and its application in bananas. First, the films were fabricated through an extrusion process with two different concentrations of TiO2 (5 and 10% w/w). Then, the films were characterized by their structural (FTIR), morphological (SEM), thermal (DSC and TGA), dynamic (DMA), barrier, and mechanical properties. The ethylene removal capacities of the samples were determined via gas chromatography and an in vivo study was also conducted with bananas for 10 days of storage. Regarding the characterization of the films, it was possible to determine that there was a higher interaction between PLA with nano-TiO2 than MB; moreover, TiO2 does not agglomerate and has a larger contact surface in PLA films. Because of this, a higher ethylene removal was also shown by PLA, especially with 5% TiO2. The in vivo study also showed that the 5% TiO2 films maintained their quality characteristics during the days in storage. For these reasons, it is possible to conclude that the films have the capacity to remove ethylene. Therefore, the development of TiO2 films is an excellent alternative for the preservation of fresh fruits. © 2024 by the authors.